Pengembangan E-Booklet Sebagai Bahan Ajar Pembelajaran Sejarah Untuk Siswa SMA - Dera Suci Tri Wahyuni; Hera Hastuti (Jurnal Kronologi, 2023)
ABSTRACT This study was motivated by the lack of diversity in teacher materials used by teachers and students, and materials for history learning are still not structured on chronological and causal relationships, suggesting historical years in history learning. The result is that students have little understanding of tables and causality. , and the teaching materials used lack the visualization of the input material and the development of Islamic religion and culture in Indonesia. The purpose of this research is to 1) develop a chronologically and causally ordered e-booklet on the process of assimilation and development of Islamic religion and culture in Indonesia, 2) analyze the feasibility of teaching materials, and 3) am. Analyze the practicality of teaching materials. This study uses a research and development (R&D) method using the ADDIE model. Data collection means used in the form of interviews and surveys. Product feasibility studies involve teaching material experts and teaching material experts. A professional teacher from SMA N 8 Padang Class X E.8 and her 33 students participated in the practical exam. In this study, the analytical techniques used are quantitative. Quantitative results were obtained through the teaching materials and the feasibility of teaching materials tools. The results of the feasibility test using the Likert scale for professionals achieved a scale of 3.66 (Very Feasible) and a percentage mark of 91.6 in category (Very Feasible); Achieved 3.81 (very viable). ) and 95.4 percentage categories (very decent). The result of the Subject Practice Test was 3.73 points (Very Practical), achieving an in-category percentage of 93.4 (Very Practical), students scoring 3.43 points (Very Practical) and 85.7% ) percentage. . Practical) Practical). Based on these results, a chronologically and causally arranged e-booklet teaching material on the process of assimilation and development of Islamic religion and culture in Indonesia is highly implementable and practical for teachers and students. It can be concluded that there is. Keywords: learning history, teaching materials,e-booklet,chronology,causality ABSTRAK Penelitian ini dilatar belakangi belum bervariasinya bahan ajar yang digunakan oleh guru dan siswa dan bahan ajar pembelajaran sejarah masih kurang disusun berdasarkan kronologis dan kausalitas yang menyebabkan siswa rendahnya akan pemahaman kronologiis dan kausalitas pada pembelajaran sejarah, dan bahan ajar yang digunakan kurangnya visualisasi pada materi proses masuk dan berkembangnya agama dan kebudayaan islam di Indonesia. Tujuan penelitian ini 1) mengembangkan e-booklet materi proses masuk dan berkembangnya agama dan kebudayaan islam di Indonesia yang disusun secara kronologis dan kausalitas, 2) menganalisis kelayakan bahan ajar 3). menganalisis kepratisan bahan ajar. Penelitian ini menggunakan metode Research and Devolopment (R&D) dengan model ADDIE. Instrumen pengumpulan data yang dipakai yaitu teknik wawancara serta angket. Untuk uji kelayakan produk dilakukannya validasi ahli materi dan ahli bahan ajar. Uji praktikalitas dilakukan oleh guru pelajaran sejarah dan 33 orang peserta didik SMA N 8 Padang kelas X E.8. Penelitian ini teknik analisis yang digunakan kuantitatif. Hasil kuantitatif didapatkan melalui instrumen kelayakan bahan ajar dan materi. Hasil uji kelayakan menggunakan skala Likert pada ahli materi diperoleh skala 3,66 (sangat layak) dan persentase 91,6% dengan kategori (sangat layak), dan uji bahan ajar diperoleh skala 3,81(sangat layak) dan persentase 95,4% dengan kategori (sangat layak). Hasil uji praktikalitas mata pelajaran yang diperoleh skala 3,73 (sangat praktis), dan persentase 93,4% dengan kategori (sangat praktis), dan pada peserta didik siperoleh skala 3,43 (sangat praktis) dam persentase 85,7%(sangat praktis). berdasarkan hasil yang di dapatkan bahwa bahan ajar e-booklet pada materi proses masuk dan berkembangnya agama dan kebudayaan islam di indonesia yang disusun secara kronologis dan kausalitas sangat layak dan praktis digunakan oleh guru dan siswa. Kata Kunci : Pembelajaran Sejarah, Bahan Ajar, E-Booklet, Kronologis, Kausalitas